EFFECT OF CEC OF CLAY ON THERMAL CONDUCTIVITY - Adeyemo Adegoke, James Adeyemo Adegoke; Egbeyale, Godwin; Akinyemi, Olukayode (Malaysian Journal of Science, 2016)
The thermal conductivity of clay doped with different concentrations of nitrate of heavy metals is presented in this study. Clay sample from Omi Adio, Ibadan, Southwestern part of Nigeria was used to investigate this work. Cation exchange, which occurs naturally with soil water, was the method explored to carry out the investigation. A microprocessor-based thermal analyzer was used to determine the thermal conductivity while Atomic absorption spectrophotometer was used to determine the heavy metal concentration. 52.0 g clay sample was mixed with 70 cm3 of nitrate of Pb (II), Cd (II), Zn (II), Cr (II), Fe (II), Hg(II), Cu (II), and Ni (II) solutions at different concentrations; after which slabs of dimensions 4cm x 4cm x 1cm were made from the mixture of the clay sample with aqueous solutions of different concentrations and the thermal conductivities determined. Thermal conductivity values were plotted against concentration of nitrate of heavy metals; 400 ppm, 800 ppm, 1600 ppm, 3200 ppm and 6400 ppm. Results showed that thermal conductivity of clay increases with increase in the concentration of heavy metal adsorbed by the clay to an optimum level. The lowest thermal conductivity was found to be 0.06W/mK (for control clay) and the highest was found to be 0.38W/mK (at 6400ppm, Copper). For all the samples, thermal conductivity increases as the concentration of heavy metals increases to a certain optimum level above which cation exchange is no longer possible. From the results, it was concluded that the increase of concentration of heavy metals adsorbed by clay during cation exchange process contributes to its thermal conductivity. Keywords: Adsorption, Clay, Concentration, Thermal conductivity, Heavy metals